Postur Tubuh dan Waktu Duduk dengan Keluhan Nyeri Punggung Bawah (LBP) - Dietha Kusumaningrum; Diana Samara; Haryo Ganeca Widyatama; ML Edy Parwanto; Dina Rahmayanti; Salsabila Ayu Widyasyifa (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction: Low back pain (LBP) is a complaint that often arises related to work and activities that can be experienced by anyone. Aim; know the relationship between posture and sitting time with complaints of low back pain (LBP) in students. Methods: A cross-sectional observational study was conducted and a total of 198 medical students. Data collection using a questionnaire, results: showed a significant relationship between head posture while sitting (p = 0.024), body mass index (p = 0.000), smoking habits (p = 0.003) and complaints of low back pain (LBP). There is no relationship between posture and knee joints when sitting, length of sitting, gender, and age with complaints of low back pain (LBP). Conclusion: There is a significant relationship between head posture (lower or upper) when sitting, body mass index (BMI), and smoking habits with complaints of low back pain (LBP).